PORTRAIT AND IMPLEMENTATION OF INTERCULTURAL COMMUNICATION COMPETENCE AT THE WORLD OF WORK - Andi Nurafni; Abdul Wahid; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
Intercultural communication is a process of exchanging information or ideas between two or more individuals from different cultural backgrounds. The purpose of this study is to identify communication patterns and assess intercultural communication competencies. The data were analyzed using a qualitative descriptive method and were collected through interviews and questionnaires. The research was conducted at Pangkalan Utama TNI AL VI. This study involved nine respondents, who are personnel or employees at Pangkalan Utama TNI AL VI. The findings indicate the presence of three communication patterns: primary, secondary, and circular communication patterns. The challenges faced by the personnel include physical barriers, differences in experience, and competition; however, these do not significantly hinder communication due to their understanding of intercultural communication competencies, which encompass motivation, knowledge, and skills.